PENGARUH KECUKUPAN MODAL DAN EFISIENSI OPERASIONAL TERHADAP PROFITABILITAS PADA PERBANKAN UMUM SYARIAH DI INDONESIA - Hasmirati Hasmirati; Alfin Akuba (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to determine and analyze how much influence capital adequacy, and operational efficiency both simultaneously and partially on profitability. This research is a quantitative study, using ratio analysis. The method of analysis uses multiple linear regression. The results showed that capital adequacy and operational efficiency simultaneously had no significant effect on profitability in Islamic general banking in Indonesia. Capital adequacy partially did not have a significant effect on profitability. Operational efficiency partially does not have a significant effect on profitability.